A study of production factors affecting seed vigour in garden peas (Pisum sativum L.) and the relationships between vigour tests and seed lot field and storage performance : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Palmerston North, New Zealand - Castillo, Abraham G. (Massey University, 1992)
Results of studies on seed vigour of 206 seed lots from six cultivars of garden peas (Pisum sativum L.), conducted at Massey University, Palmerston North, New Zealand are reported in this thesis. The relationship between vigour tests and field emergence of garden pea seed lots with varying seed quality characters was evaluated in 1988 for 82 seed lots from six cultivars under unirrigated conditions and under both irrigated and unirrigated conditions in 1989 for 23 seed lots from three cultivars (Section One). Vigour of seeds produced from various plant populations, row spacings, sowing times, methods of harvest and pod positions from field experiments in the 1988-1989 and 1989-1990 cropping seasons was recorded from 96 seed lots for two cultivars (Section Two). The performance of five seed lots of varying seed quality characters stored under eight different conditions formed the basis for a discussion of potential storage, relative storability and prediction of storage life in garden peas (Section Three). Stressful conditions, i.e. extremely dry or very wet conditions, can limit germination and field emergence in garden peas. The 1988 environment (favourable rainfall and temperature) allowed good field emergence. However, low rainfall in November 1989 (unirrigated sowings) and excessive water following rain at the 30 October and 20 December 1989 (irrigated) sowings, caused reductions in field emergence. The germination test was strongly correlated with field emergence when conditions for sowing were favourable and when low germinating seed lots were included in the analysis. However, when low germinating seed lots (less than 85%) were excluded, the relationship between germination and field emergence was low and unreliable. Differences in field emergence between seed lots were a reflection of differences in vigour which were detected by the conductivity test. The conductivity test was strongly correlated with field emergence of garden pea seed lots under all sowing conditions. Expected field emergence (EFE) did not differ from the conductivity test for cv. Small Sieve Freezer under stress conditions, but it did not predict field emergence under all sowing conditions and for all cultivars. Multiple linear regression equations derived from the results differed among cultivars and for various sowing conditions, but none resembled the EFE equation currently used commercially. Removing the hollow heart effect from the EFE increased the relationship between EFE and field emergence under favourable conditions but reduced the relationship under stress conditions. Hollow heart is therefore an important component of seed lot performance under stress sowing conditions. In order to include the effect of hollow heart in the prediction of field emergence, EFE should be used. Further, use of EFE allows the determination of the quantity of seed needed for sowing to achieve a specific population, which the conductivity test result alone cannot provide. The EFE approach should be further evaluated. Conductivity and controlled deterioration test results illustrated seed vigour differences resulting from various production practices i.e.: - seeds from a population of 200 plants m-2 and a 10 cm row width harvested at 15% seed moisture content (SMC) had lower vigour than less dense plantings. Furthermore, there was a high hollow heart incidence, especially in bottom pod seeds. At lower population densities (50 and 100 plants m-2), the top pod seeds harvested at 15% SMC had higher leachate conductivity than the bottom pod seeds. These effects on seed quality were attributed to high temperature and RH within the crop canopy. The temperature within the crop canopy was 2°C - 5°C higher than the air temperature, especially at the 200 plants m-2 population density. The relative humidity within the canopy at the 200 plants m-2 population density was 5% - 10% higher than within the canopy at the 50 and 100 plants m-2 population densities. - seeds harvested at 40% SMC were of low vigour when machinery was used in harvesting. Although the seeds had attained physiological maturity, they were prone to damage when harvested at this seed moisture content. Higher vigour seeds were produced when harvesting was done at 25% SMC than at 15% SMC, even when machinery was used. - seeds from a December sowing were higher in vigour than seeds from a November sowing, which was attributed to a more favourable environment during seed development and maturity. For the later sowing, seeds developed and matured during February / March when the temperature (2°C - 5°C lower than January) and RH (5% - 10% lower than January) were more suitable for seed development. - seed deterioration in the field was increased by windrowing because during the time seeds were in the swath prior to harvest, they were exposed to high temperature and relative humidity. Decline in germination and field emergence was faster in low vigour seed lots than high vigour seed lot in all storage conditions. Results from the conductivity and controlled deterioration tests (vigour tests) provided better data for determining potential storability in garden peas than the germination test. The conductivity and 6 day CD tests had the best relationships in most of the controlled storage conditions and were good predictors of germination and field emergence after storage. However, better prediction of storage life was obtained under controlled storage conditions than under ambient storage conditions, probably because of greater uniformity in the germination decline. Further work is required to develop a test for predicting storage life in ambient conditions. Probit analysis of the decline in germination under the eight different storage conditions produced variable results. Under controlled storage (e.g. 25°C / constant 13% SMC) which produced a high decline in germination, the germination data when transformed into probits followed a curve, rather than the expected straight probit line for all seed lots. This may be attributed to the indeterminate character of peas which causes variable seed quality parameters at harvest, and therefore the production of heterogeneous seed lots. The data suggest that the probit model is not entirely appropriate for the prediction of storage life in garden peas, and more work is required to determine the effect of heterogeneity on storage performance.
Keywords: Peas; Pea seeds; Pea growth; Pea storage